BUYING AND SELLING FROM THE PERSPECTIVE OF THE QURAN AND HADITH - Fattah, Abdul (PT. Anagata Sembagi Education, 2024)
Buying and selling in Islam is not only an economic transaction, but also has a spiritual and ethical dimension that distinguishes it from other economic systems. This study aims to examine the interpretation of verses and hadith ahkam on buying and selling, to understand the principles and ethics underlying economic transactions in Islam. This study uses a qualitative approach with a literature study method. The primary data sources are the Qur'an and hadith, while secondary data sources include tafsir books, hadith explanations, fiqh books, and relevant journal articles. The results of the study indicate that buying and selling in Islam must be based on principles such as willingness, justice, honesty, and transparency. In addition, there are ethics that must be considered, such as avoiding usury, gharar (uncertainty), and fraud. This study is expected to provide a better understanding of buying and selling in Islam, so that Muslims can carry out their economic activities in accordance with religious guidance and achieve blessings in every transaction.